Synchronous machines parameters identification using load rejection test data - da Costa Bortoni, Edson [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1997)
This work shows a computational methodology for the determination of synchronous machines parameters using load rejection test data. The quadrature axis parameters are obtained with a rejection under an arbitrary reference, reducing the present difficulties.
Keywords: Load rejection test data; Algorithms; Electric loads; Mathematical models; Numerical methods; Parameter estimation; Synchronous machinery